2013
DOI: 10.2147/cia.s35926
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electromagnetic field therapy for management of osteoarthritis-related pain, stiffness and physical function: clinical experience in the elderly

Abstract: BackgroundPulsed electromagnetic field (PEMF) therapy has shown promising therapeutic effectiveness on bone- and cartilage-related pathologies, being also safe for management of knee osteoarthritis.AimThe aim of this study was to investigate the clinical efficacy of a PEMF device for management of knee osteoarthritis in elderly patients.Materials and methodsA total of 33 patients were screened, and 28 patients, aged between 60 and 83 and affected by bilateral knee osteoarthritis, were enrolled in this study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 35 publications
(25 reference statements)
2
39
0
1
Order By: Relevance
“…Alternative approaches to improve regeneration capacity in explants treated with PEMFs may include: 1) increasing exposure amplitude; 2) increasing exposure duration; 3) increasing number of exposures to a value greater than 1; 4) exposing MSC-seeded explants directly to PEMFs or; 5) a combination of the above. In fact, Esposito et al have previously reported induction of chondrogenic differentiation upon PEMF treatment [14] and several in vivo studies have demonstrated beneficial effects of this therapy on clinical symptoms of animals and humans with osteoarthritis [11,12]. It has to be mentioned though that these studies applied 6 weeks of daily treatment of the injured joint, whereas our study employed single 10 minute prestimulation of chondrogenically induced MSCs and unstimulated ex vivo cartilage explants.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Alternative approaches to improve regeneration capacity in explants treated with PEMFs may include: 1) increasing exposure amplitude; 2) increasing exposure duration; 3) increasing number of exposures to a value greater than 1; 4) exposing MSC-seeded explants directly to PEMFs or; 5) a combination of the above. In fact, Esposito et al have previously reported induction of chondrogenic differentiation upon PEMF treatment [14] and several in vivo studies have demonstrated beneficial effects of this therapy on clinical symptoms of animals and humans with osteoarthritis [11,12]. It has to be mentioned though that these studies applied 6 weeks of daily treatment of the injured joint, whereas our study employed single 10 minute prestimulation of chondrogenically induced MSCs and unstimulated ex vivo cartilage explants.…”
Section: Discussionmentioning
confidence: 93%
“…In 28 elderly humans with bilateral knee osteoarthritis, PEMF stimulation at 3 times per week over 6 weeks significantly improved pain, stiffness, and physical function in comparison to the untreated contralateral joint [12]. Trock et al found that treating human patients with knee osteoarthritis (n=86) with PEMFs for a total of 18 times caused significant differences in pain, pain on motion, and tenderness in comparison to placebo treatments [13].…”
Section: Introductionmentioning
confidence: 99%
“…PEMF has been utilized in clinical studies to treat osteoarthritis, epicondylitis, and rotator cuff tears. 9,18,19,26 At three months post-op, patients with small or medium rotator cuff tears showed improved range of motion after receiving PEMF therapy when compared to those receiving placebo. In order to investigate the structural and functional effects of PEMF on tendon-to-bone healing, we have previously utilized PEMF in a rat rotator cuff injury and transosseous repair model.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to recent progress in nanomedicine and molecular biology, we can begin to understand the signalling pathways involved in mechanotransduction and exploit them with magnetic actuation for a myriad of applications: stem cell differentiation and homing to injury sites, as well as tissue engineering strategies [19][20][21][22][23][24][25]. In tissue engineering, magnetic actuation can allow for better seeding in 3D scaffolds [26][27][28], and can be used in scaffold-free approaches to build tissues bottom-up from mesenchymal stem cells (MSCs) or induced pluripotent stem cells (iPSCs) [29][30][31].…”
mentioning
confidence: 99%